The Principle and Limits of the Protection of Life in Rabbinic Jurisprudence and Practice - Ruff, Tibor (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2025)
This paper examines the interpretative framework within the principle of the protection of life in Jewish law since the Maccabean wars, has been put into practice. The principle, which covered not only the imminent danger to one’s life but also the protection of health, provides insights into the internal hierarchical order of the commandments, the relationship between the written Torah and the oral Torah, the relationship of Jesus to the oral Doctrine, and the factors that shaped Jewish tradition in Jesus’ era and in the centuries leading up to the compilation of the Talmud.